A Música Como Recurso Pedagógico Na Educação Infantil: Limites e Possibilidade do Trabalho Docente - Sousa, Welderjane Monteiro Dourado (Universidade Federal do Tocantins, 2022)
The main objective of this work is to explain the pedagogical character of music in early childhood education at a CMEI (Centro Municipal de Educação Infantil) in Palmas TO. It started from the problematization that music has been used only for entertainment. However, its educational potential can be harnessed when a pedagogical sense is attributed in early childhood education activities. The work is the result of reflections on the formative experience of the pedagogical residency program and the readings of the theme in educational journals. Musical experiments were carried out in the classroom and the results demonstrate that music educates children's sensitivity. I highlight the need for continuing education that helps teachers and think about strategies on how to use music from a pedagogical perspective.